2018
DOI: 10.1186/s12967-018-1639-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of invasion-metastasis-associated microRNAs in hepatocellular carcinoma based on bioinformatic analysis and experimental validation

Abstract: BackgroundHepatocellular carcinoma (HCC) is one of the most lethal cancer, mainly attributing to its high tendency to metastasis. Vascular invasion provides a direct path for solid tumor metastasis. Mounting evidence has demonstrated that microRNAs (miRNAs) are related to human cancer onset and progression including invasion and metastasis.MethodsIn search of invasion-metastasis-associated miRNAs in HCC, microarray dataset GSE67140 was downloaded from the Gene Expression Omnibus database. Differentially expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 31 publications
(27 reference statements)
0
64
0
Order By: Relevance
“…For early cases, hepatectomy is effective; whilst for advanced cases, systemic therapy including radiofrequency ablation, microwave ablation, percutaneous ethanol injection, transcatheter arterial chemoembolization and transplantation may not improve the poor prognosis [13]. Extensive local invasion and distant metastasis are the major reasons of deaths in patients with HCC [14,15]. Therefore, the prognostic and predictive biomarkers of tumor migrate and progression is eagerly wanted for the improvement of HCC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For early cases, hepatectomy is effective; whilst for advanced cases, systemic therapy including radiofrequency ablation, microwave ablation, percutaneous ethanol injection, transcatheter arterial chemoembolization and transplantation may not improve the poor prognosis [13]. Extensive local invasion and distant metastasis are the major reasons of deaths in patients with HCC [14,15]. Therefore, the prognostic and predictive biomarkers of tumor migrate and progression is eagerly wanted for the improvement of HCC outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Kaplan-Meier plotter database is capable to assess the effect of miRNAs and genes on survival in 21 cancer types, including hepatocellular carcinoma (21). The prognostic values of potential miRNAs in hepatocellular carcinoma was evaluated using Kaplan-Meier plotter (http://kmplot.com/analysis/) as we previously described (22,23). In brief, each miRNA of interest was first entered into this database.…”
Section: Kaplan-meier Plotter Analysismentioning
confidence: 99%
“…Besides, clinical characteristics among VCX3A and HCC in TCGA also showed that high expression of VCX3A was more likely to cause vascular invasion in HCC patients (Table 1). Identifying hsa-miR-664a-3p-VCX3A axis play a key role in HCC First, we predicted upstream miRNAs of VCX3A through TargetScan, miRWalk and miRDB three databases, since increasing studies have indicated that miRNAs take part in the invasion and metastasis of multiple tumors and play signi cant functions in cancer development [15][16][17]. As presented in Figure 4A-B, a total of 15 miRNAs (hsa-miR-2861, hsa-miR-5739, hsa-miR-4505, hsa-miR-6770-3p, hsa-miR-7855-5p, hsa-miR-4299, hsa-miR-6871-3p, hsa-miR-31-5p, hsa-miR-181a-5p, hsa-miR-450b-5p, hsa-miR-3615, hsa-miR-5696, hsa-miR-664b-3p, hsa-miR-579-3p, hsa-miR-664a-3p) appeared twice or more than twice in three predicting databases were selected for the further analysis.…”
Section: Resultsmentioning
confidence: 99%